Impacts of economic crises on e-commerce in Czech Republic - Kristína Korená; Petra Pártlová; David Vyšín; Vít Kluger; Michal Ruschak (Entrepreneurship and Sustainability Issues, 2024)
E-commerce has been undergoing intensive development every year to match the development of information and communication technologies. E-commerce has a significant, yet diverse, impact on the analysis of selected e-commerce segments during the COVID-19 pandemic between 2021 and 2022. Metadata evaluated our results using the tools of Google Analytics, Google AdSense, and Supermetrics tool. The research involved structured interviews to refine and improve the results obtained. We also analysed the turnover and year-on-year changes of selected e-shops in beauty products, food, fashion accessories, and luxury goods, exploring the development trends related to the pandemic and the ongoing war conflict. A part of the solution was also the analysis of the tested segments in terms of the NUTS 3 regions and the specification of the development of the business segment under review from the perspective of the geographical regional location. The obtained data will provide experts and the business sector with information about the development of e-commerce during times of crisis. They also apply to existing and potential business entities regarding their position in an increasingly challenging market environment. The first approximation of the results will be refined and validated in further research.